A Study of Psychosocial Factors Related to Preserving Thai Traditions of Undergraduate Students - Sitsira-at, Shuttawwee (International Journal of Engineering and Technology, 2018)
This correlational comparative study aimed at investigating important psychological and situational predictors of preserving Thai traditions, as well as, finding the groups at risk of not preserving Thai traditions. The sample of 1,297 undergraduate students from 10 universities in junior and senior levels was obtained. The sample consisted of 265 male students and 1,032 female students. The stratified quota random sampling was used. The hypotheses are tested by Multiple Regression analysis. Results of the research found that the positively correlation between studentsâ€™ psychological traits, social situations, psychological states and preserving Thai traditions is statistically significant at .01. Results of the total sample from multiple regression analysis indicated that behavioral intention to Thai-value was the first important predictor of this behavior, followed by social norm, cultivated by families, opening for information, role model, core-self-evaluation, attitude toward Thai products, psychological immunity, perceived ease of shopping Thai products, ego identity, and Future orientation and self-control with the accuracy of 45.3%. The highest predictive percentage of 31.6% was found in male students with the same important predictors as the total group. Furthermore, the results showed that male in senior students were the groups at risk of not preserving Thai traditions. Â Â Â Â Â Â